PREVALENCE OF BOOPHILUS SP. TICKS INFESTATION ON BALI CATTLE IN BADUNG DISTRICT - Rustam, Chairannisa; Dwinata, I Made; Suratma, Nyoman Adi (Buletin Veteriner Udayana, 2021)
Bali cattle are native Indonesian germplasm that has the advantage of survival in an inadequate environment, but Bali cattle can also contract diseases; one of them is ectoparasites, namely ticks. Cow tick or Boophilus sp. is a blood-sucking ectoparasite that causes anemia in these animals. Besides sucking blood, Boophilus sp. also a vector of various blood parasitic diseases, including Babesiosis ( Babesia bovis and B. bigemina ) and Anaplasmosis ( Anaplasma marginale ). Factors that can influence ticks Boophilus sp. in cattle, namely age, sex, maintenance, and environment. The aim of this study was to determine the prevalence and predilection of infesting bali cattle in Badung Regency, as well as the relationship of sex, age, maintenance, and environmental factors to the infestation of Boophilus sp. The research sample was taken in Badung Regency, determined purposively with a sample of 300 Bali cattle. This study was an observational study with a cross-sectional design. The results showed that the prevalence of tick infestation Boophilus sp. in Badung Regency is 7.7%. Predilection was found in the legs (40%), udder (25%), abdomen (17%), back (12%), and head (6%). Age, maintenance, and environmental factors were very influential (P <0.05) on tick infestations of Boophilus sp. in Bali cattle in Badung Regency, but gender has no effect (P> 0.05).